Made in Africa Learning to Compete in Industry - Page, John; Newman, Carol; Rand, John (Brookings Institution Press, 2016)
Why is there so little industry in Africa? Over the past forty years, industry and business interests have moved increasingly from the developed to the developing world, yet Africa's share of global manufacturing has fallen from about 3 percent in 1970 to less than 2 percent in 2014. Industry is important to low-income countries. It is good for economic growth, job creation, and poverty reduction. Made in Africa: Learning to Compete in Industry outlines a new strategy to help Africa gets its fair share of the global market. Here, case studies and econometric and qualitative research from Africa, as well as emerging Asia, help the reader understand what drives firm-level competitiveness in low-income countries.
Description based on print version record.
KU Select 2018: HSS Backlist Books
Keywords: Business & Economics / Development / Economic Development; Economics; Electronic books